Transient Receptor Potential Melastatin 8 (TRPM8)-Based Mechanisms Underlie Both the Cold Temperature-Induced Inflammatory Reactions and the Synergistic Effect of Cigarette Smoke in Human Bronchial Epithelial (16HBE) Cells - Wang, Jing; Yang, Gang; Li, Minchao; Zhou, Xiangdong (Frontiers in Physiology, 2019)
Transient receptor potential melastatin 8 (TRPM8) is a major receptor of cold environment. Recently, we found that cigarette smoke extract (CSE) upregulated TRPM8 mRNA and protein expression in bronchial tissues that made them more sensitive to cold stimuli. In our present study, we found that cold temperature(18°C)-induced activation of TRPM8 in 16HBE cells facilitated Ca2+ influx and subsequently led to the increased expression of IL-6, IL-8, and TNF-α via the upregulation of p-extracellular signal-regulated kinase (ERK) and the activation of NF-κB. In addition, 16HBE cells that co-stimulated with 18°C and CSE were used to explore the synergistic effect of CSE on cold temperature-induced inflammatory cytokine production as well as the possible involved signaling pathway. RT-PCR and western blot analysis revealed that CSE upregulated TRPM8 mRNA and protein level in 16HBE cells. Ca2+ imaging, western blot and luciferase assay showed more robust increase in intracellular Ca2+ and promoted phosphorylated ERK, P38, and NF-κB activity respectively in 16HBE cells co-stimulated with CSE and cold temperature, and such alteration was attenuated by TRPM8 shRNA transfection and BCTC pretreatment. Furthermore, enhanced levels of IL-6, IL-8 and TNF-α showed by ELISA were reduced by specific inhibitors of ERK and NF-κB. Collectively, our results suggest that mitogen-activated protein kinase (MAPK)/NF-κB signaling is involved in TRPM8-mediated cold temperature-induced inflammatory cytokine expression. In addition, CSE synergistically amplifies cold temperature-induced inflammatory factors release via upregulating TRPM8 expression and enhancing MAPK/NF-κB signaling pathway.